A cross-layer scheme for resource reservation based on multi-protocol label switching over mobile IP version6 - Malekian, Reza; Abdullah, Abdul Hanan; Saeed, Rashid Abdelhaleem (Academic Journals, 2011)
The last decades have brought tremendous improvement in wireless internet and its technologies. This has inspired the development of a variety of new services in business and consumer markets. The real time applications such as voice over internet protocol (VOIP) and other multimedia traffic such as Internet Protocol television have driven the demand for increasing and guaranteed bandwidth requirements in the network. Due to the mobility feature within a MN, mobile networks need a more sophisticated mechanism for quality of service provision. Beside, custom routing methods in a Mobile IPv6 network deliver a packet via specific tunnel. In the tunnel, intermediate routers are incapable to retrieve necessary information for guarantee quality of service due to adding headers in IPv6-in-IPv6 encapsulation. The purpose of this paper is to propose an approach to guarantee end-to-end QoS over Mobile IPv6 networks. This research paper focuses on tunnel redundancy in routing mechanisms over Mobile IPv6. In this paper, we propose a cross layer scheme to overcome negative effect of tunneling over Mobile IPv6 networks whenever a RSVP messages traverse via tunneling.